DUALISM OF ECONOMIC AND DEMOGRAPHIC INTERESTS OF THE STATE IN THE CONTEXT OF ALCOHOLIC MARKET REGULATION: HISTORY AND PRESENT - M. Sumenkova (Гуманитарные и юридические исследования)
The problem of regulating the turnover of alcohol and the existence of the alcohol market at all times attracted genuine attention, both from the side of state power structures, and from the side of society and individuals. The concentration of economic, demographic, legal, moral interests inevitably determines the relevance and topicality of the study of issues of regulation of production, consumption and sale of alcoholic beverages. The dilemma between the need to replenish the state budget and prevent degradation of the population, the preservation of somatic and mental health of people actualizes the theme stated in the article. The sci-entiic novelty is due to the very statement of the problem, as well as the fact that the author subjects the state alcohol policy of imperial Russia of the beginning of the 20th century to a comparative analysis with similar activities, but in the modern period. It is noted that over the past centuries, most of the problems have remained the same, only the means of resolving them have partially changed. The author, pointing to the undoubted achievements of the modern Russian state in streamlining the sphere under consideration, at the same time suggests using some of the positive achievements of the imperial government. The object of the study is social relations that arise and change under the influence of regulation of the alcohol market. The issues of treasury wine monopoly, which had an undoubted positive impact on the state of turnover of school drinks in the analyzed period, are investigated in detail. The conflict between the requirements of producers of alcoholic beverages, supported by the provisions of economic feasibility and the desire of the state to optimize the demographic situation, is examined. The subject of the study is speciic economic and demographic indicators that are directly related to the process of production and consumption of alcoholic beverages. The aim of the study is to analyze the regulation of the alcohol market associated with the development of speciic practical proposals aimed at its optimization. The main methods used by the authors are dialectical materialism, the system-structural method, the historical method, and the logical method.